Modern saints : their lives and faces. - Ball, Ann, 1944-2008 (Tan Books and Publishers, Inc., 1983)
1. Saint Julie billiart . -- 2. Blessed Philippine Duchesne. -- 3. Saint Joaquina. -- 4. Saint Dominic Savio. -- 5. Saint john Neumann. -- 6. Saint Gabriel possenti. -- 7. Saint Benildus. -- 8. Henriette Delille. -- 9. Francis seelos. -- 10. Saint Peter Julian Eymard. -- 11. Saint Anthony Mary Claret. -- 12. Saint Bernadette Soubirous. -- 13. Saint Mary Mazzarello. -- 14. Saint Charles Lwanga and Companions. -- 15. Saint Soledad. -- 16. Saint John Bosco. -- 17. Father Damien. -- 18. Augustus Czartoryski. -- 19. Agostina Pietrantoni. -- 20. Andrew Beltrami. -- 21. Saint Charbel. -- 22. Maria Droste Zu Vischering. -- 23. Mother Angela Truszkowska. -- 24. Blessed Gregory and Companions. -- 25. Saint Maria Goretti. -- 26. Saint Gemma Galgani. -- 27. Laura Vicuna. -- 28. Zepherin Namuncura. -- 29. Mother Mary Magdalen Bentivoglio. -- 30. Teresa Valse Pantellini. -- 31. Brother Miguel. -- 32. Michael Rua. -- 33. Louis Guanella. -- 34. Brother Isidore of Saint Joseph. -- 35. Charles de Foucauld. -- 36. Saint Frances Cabrini. -- 37. Blessed Mary Fortunata Viti, O.S.B. -- 38. Mother Mary Walsh. -- 39. Saint Raphaela. -- 40. Rose Hawthorne Lathrop. -- 41. Sister Miriam Teresa. -- 42. Father Miguel Pro. -- 43. Fhater Lukas Etlin. -- 44. Bishop Luigi Versiglia and Father Callisto Caravario. -- 45. Sister Carmen Moreno and Sister Amparo carbonell. -- 46. Brother Andre. -- 47.Don Louis Orione. -- 48. Saint Maximilian Kolbe. -- 49. Titus Brandsma. -- 50. Edith Stein. -- 51. Sister Alphonsa. -- 52. Maria Teresa Quevedo. -- 53. Mary Ann Long. -- 54. Padre Pio. -- 55. Brother Elias.